If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 5) = -2(x + 1) Reorder the terms: 4(5 + x) = -2(x + 1) (5 * 4 + x * 4) = -2(x + 1) (20 + 4x) = -2(x + 1) Reorder the terms: 20 + 4x = -2(1 + x) 20 + 4x = (1 * -2 + x * -2) 20 + 4x = (-2 + -2x) Solving 20 + 4x = -2 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 20 + 4x + 2x = -2 + -2x + 2x Combine like terms: 4x + 2x = 6x 20 + 6x = -2 + -2x + 2x Combine like terms: -2x + 2x = 0 20 + 6x = -2 + 0 20 + 6x = -2 Add '-20' to each side of the equation. 20 + -20 + 6x = -2 + -20 Combine like terms: 20 + -20 = 0 0 + 6x = -2 + -20 6x = -2 + -20 Combine like terms: -2 + -20 = -22 6x = -22 Divide each side by '6'. x = -3.666666667 Simplifying x = -3.666666667
| 3tan^2(pi)-1=0 | | -8(6k+4)=-128 | | 16x^2-32x+18=0 | | -16g+3h-19h-4g-16h= | | j+2=9 | | 42y=32x+340 | | -40-(2x+5)=-60 | | t=(3.28+7.18)4.6 | | 3x+2-4(x+1)=5x+22 | | 2(5x-6)+6(5x-7)=-54 | | 6.05=2.25m+.2 | | 3G-2(g+4)=8g-8 | | 12(2p-3)=99-9p | | -(-8x-7m)=5m-7(-3-1m) | | 60=6(6-12n) | | x+2-4(x+1)=5x+22 | | -7x/5=3/10 | | 7x+5=5x+16 | | 1+7p-7p=4 | | 7y=3y+32 | | -(7x/5)=3/10 | | -5=-x+5y | | d+-3=-10 | | 4x+6.66666666666666666666666666y=500 | | f=4(3+4)-2 | | 2x+16=4x-15 | | -7x+3y=7 | | u-5=11 | | -4p+29=13 | | 5.5+2=d | | C=50p | | -4n+1=17 |